2021
DOI: 10.3390/cells10030688
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs Potentially Involved in Post Lung Transplant-Obliterative Bronchiolitis: The Role of miR-21-5p

Abstract: Epigenetic changes, including miRNAs deregulation, have been suggested to play a significant role in development of obliterative bronchiolitis (OB) in transplanted lungs. Many studies have tried to identify ideal candidate miRNAs and the downstream pathways implicated in the bronchiolar fibro-obliterative process. Several candidate miRNAs, previously indicated as possibly being associated with OB, were analyzed by combining the quantitative real time-polymerase chain reaction (qRT-PCR) and in situ hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Many studies have tried to identify miRNA ideal candidate, and the downstream pathways implicated in the bronchiolar fibro-obliterative process [17]. Different studies evaluated the immunomodulatory effect of ECP therapy in patients after solid organ transplant rejection [18][19][20][21][22], but few studies have explored the molecular regulation associated with ECP treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to identify miRNA ideal candidate, and the downstream pathways implicated in the bronchiolar fibro-obliterative process [17]. Different studies evaluated the immunomodulatory effect of ECP therapy in patients after solid organ transplant rejection [18][19][20][21][22], but few studies have explored the molecular regulation associated with ECP treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…En pacientes con trasplante de pulmón se observó una correlación entre la sobreexpresión de miR-21 y el proceso fibro-obliterativo de múltiples trastornos involucrados con fibrosis, entre ellos la disfunción crónica de aloinjerto pulmonar, enfermedad que limita la supervivencia de pacientes trasplantados. El aumento en la expresión de miR-21 suele preceder la instauración de síndrome de bronquiolitis obliterante, lo que alienta a continuar su estudio en esta patología (30).…”
Section: Enfermedades Pulmonaresunclassified
“…Several studies have attempted to identify specific miRNAs associated with CLAD development, with pro-fibrotic miRNA-21 being the most promising candidate [70][71][72]. Its co-over expression with signal transducer and activator of transcription 3 could play a role in the development of obliterative bronchiolitis [73]. In a small pilot study, miRNA-21 showed a good discriminative power (AUC of 0.89) in confirming a CLAD diagnosis.…”
Section: Mirna and Cladmentioning
confidence: 99%